(untitled) (Baghdad Science Journal, 2024)
The present study included the microscopic and molecular identification of Entamoeba histolytica by using specific primers to detect four virulence factors possessed by Entamoeba histolytica. Virulence factors included Active Cysteine proteinase, Galactose/N-acetyl-D-galactose-lectin, Amoeba pore C and Phospholipase. Titanium dioxide nanoparticles (TiO2NPs) were synthesized from Pseudomonas aeruginosa which producing Pyocyanin pigment as a reducing agent to form it. After that we studied the ability ofTiO2NPs to inhibit virulence factors production and curing the genes responsible for encoding them by using four different dose 2 ,3, 4, 6 mg/Kg and administered by intraperitoneal injection to laboratory mice Mus musculus. The infection was molecularly confirmed, then the treatment for a period of ten days, as it was given on the third, fifth, seventh, and tenth days. The results of the study showed the inability of dose 2, 3 mg/Kg of TiO2NPs to curing the gene responsible for active cysteine ​​proteinase and Gal/Gal NAC lectin upon treatment on the third to the tenth day, but was able to curing the genes when using dose (4,6) mg/Kg, Statistical analysis was performed , it was found that there were significant differences between the use of different dose and days of treatment. While Amoeba pore C, it was found that the four dose did not affect the inhibition on the third day of treatment. While dose 4,6 mg/Kg were able to curing the gene responsible for its encoding. Statistical analysis showed significant differences between the use of TiO2NPs and the days of treatment. Finally, the results showed that the four doses do not affect on phospholipase. Once, performing the statistical analysis it was found that there were no significant differences.